Some Challenges in Using Multilayer Networks to Bridge Brain and Mind. - Vitevitch, Michael S. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2025)
The application of techniques from network science to create single-layer networks of the brain and mind has resulted in significant advances in the neuro- (i.e., structural and functional brain networks) and cognitive sciences (i.e., cognitive network science). Recent advances in network science on multilayer networks increase the possibility that a "network of networks" might finally connect the physical brain to the intangiblemind, much like physical fibre optic cables and wires connect to other layers of the internet to allow intangible social networks to form in various social media platforms. Several advances in structural brain networks, functional brain networks, cognitive networks, and multilayer networks are briefly reviewed. The possibility that these single-layer networks can be connected in a multilayer network to connect the brain to the mind is discussed, as well as some of the challenges that face such an ambitious endeavour.